2021
DOI: 10.1039/d1nr02881b
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-like bacterial death modulated by photoactive hyperthermia nanomaterials and enhanced wound disinfection application

Abstract: Photothermal therapy (PTT) is considered as one efficient therapeutic strategy for wound disinfection. However, there is a dilemma that high PTT temperature for killing bacteria (>58 °C) could pose serious...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…It is well-known that bacteria are composed of a variety of lipid types . The bacterial lipid metabolite changes convey much valuable information on the interactions between antibacterial treatment and bacteria. , Previous reports revealed that the high temperature in conventional PTT could disrupt the enzyme activity and phospholipids on the cell membrane. , The activity of antibacterial agents also depends on their interaction with bacterial membranes . However, there are few investigations about the change of lipid molecular pattern when treated with different therapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that bacteria are composed of a variety of lipid types . The bacterial lipid metabolite changes convey much valuable information on the interactions between antibacterial treatment and bacteria. , Previous reports revealed that the high temperature in conventional PTT could disrupt the enzyme activity and phospholipids on the cell membrane. , The activity of antibacterial agents also depends on their interaction with bacterial membranes . However, there are few investigations about the change of lipid molecular pattern when treated with different therapy.…”
Section: Resultsmentioning
confidence: 99%
“…64,65 Previous reports revealed that the high temperature in conventional PTT could disrupt the enzyme activity and phospholipids on the cell membrane. 66,67 The activity of antibacterial agents also depends on their interaction with bacterial membranes. 62 However, there are few investigations about the change of lipid molecular pattern when treated with different therapy.…”
Section: Loading and Antioxidant Activity Of Cur In Cuppsimentioning
confidence: 99%
“…Comparing with visible light, NIR with wavelength ranging from 780 to 2500 nm is featured with deeper tissue penetration and invasiveness [98]. Thus, NIR-based PTT has been extensively explored for anti-infective therapy [99][100][101]. The photothermal nanoagents can absorb the NIR and convert the optical energy into heat, which then initiates the cell membrane breakage and protein denaturation in bacteria, finally leading to their thermal ablation [102][103][104].…”
Section: Nir Stimulationmentioning
confidence: 99%
“…Specifically, gold nanorods (AuNRs) exhibit advantageous high photothermal conversion efficiency at the therapeutic window of the near-infrared (NIR) region, which is not absorbed by most living tissues [ 8 , 9 ]. The mechanism of APTT is still unraveling, with reports indicating thermal damage [ 10 ], as well as bacterial membrane disruption (but not necessarily rupture) [ 11 ], and even the localized formation of reactive oxygen species [ 12 ]. Furthermore, the bulk temperature elevation associated with APTT is ~20 °C lower than that required for simple thermal bacterial inactivation [ 11 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of APTT is still unraveling, with reports indicating thermal damage [ 10 ], as well as bacterial membrane disruption (but not necessarily rupture) [ 11 ], and even the localized formation of reactive oxygen species [ 12 ]. Furthermore, the bulk temperature elevation associated with APTT is ~20 °C lower than that required for simple thermal bacterial inactivation [ 11 , 13 , 14 , 15 ]. The lower temperature required is advantageous, as excessive tissue heating and damage could be minimized [ 11 ].…”
Section: Introductionmentioning
confidence: 99%